2014
DOI: 10.1039/c3dt53529k
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and structural studies of an unexplored monoamide, N,N′-dioctyl, α-hydroxy acetamide with lanthanide(iii) and actinide(iii) ions

Abstract: A monoamide, N,N'-dioctyl, α-hydroxy acetamide, shows unusual extraction properties towards trivalent lanthanide and actinide ions above 3 M HNO3. The extracted ions could be quantitatively back extracted using 0.5 M HNO3. This amide shows negligible extraction towards Sr(II) and Ru(III) ions, making it advantageous over other reported extractants. The structures of Sm(III) and Eu(III) nitrate compounds show that the metal ion is surrounded by three of the ligands, one nitrate and one water molecule. The ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…Therefore, the distribution ratio of both U(VI) and Pu(IV) increases with increase in the concentration of nitric acid. Similar results were also reported by Kannan et al [22] for the extraction of U(VI) and Pu(IV) in 0.2 M DOHyA/n-DD. The distribution ratio of U(VI) and Pu(IV) in 0.2 M DOHyA/n-DD increased with increase in concentration of nitric acid and continued to increase up to 10 M HNO 3 [22], investigated in that study.…”
Section: Effect Of Aqueous Nitric Acid Concentration On the Extractiosupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the distribution ratio of both U(VI) and Pu(IV) increases with increase in the concentration of nitric acid. Similar results were also reported by Kannan et al [22] for the extraction of U(VI) and Pu(IV) in 0.2 M DOHyA/n-DD. The distribution ratio of U(VI) and Pu(IV) in 0.2 M DOHyA/n-DD increased with increase in concentration of nitric acid and continued to increase up to 10 M HNO 3 [22], investigated in that study.…”
Section: Effect Of Aqueous Nitric Acid Concentration On the Extractiosupporting
confidence: 90%
“…Similar results were also reported by Kannan et al [22] for the extraction of U(VI) and Pu(IV) in 0.2 M DOHyA/n-DD. The distribution ratio of U(VI) and Pu(IV) in 0.2 M DOHyA/n-DD increased with increase in concentration of nitric acid and continued to increase up to 10 M HNO 3 [22], investigated in that study. Figure 5 shows the UV-VIS absorption spectrum of uranium obtained by the extraction of U(VI) present in 4 M nitric acid by a solution of 0.5 M DOMeOA in n-dodecane.…”
Section: Effect Of Aqueous Nitric Acid Concentration On the Extractiosupporting
confidence: 90%
“…10 that the data corresponding to the Pu IV sorption isotherm by DOHA-PP SLM showed a higher correlation coefficient with the Langmuir model, indicating that the Pu IV sorbed on the membrane is chemically bonded to the N , N ′-dioctyl-α-hydroxyacetamide ligand. This is in agreement with the previous literature report, that DOHA acts as a bidentate ligand and forms a coordination bond with the actinides through the OC–CH 2 –OH moiety. The equilibrium sorption capacity of the membrane for Pu IV calculated from the Langmuir isotherm was found to be 23.82 mg/g of the membrane, which was in good agreement with the experimentally determined uptake capacity given in Table , i.e., 23.11 mg/g.…”
Section: Resultssupporting
confidence: 94%
“…The monoamide DOHA ligand was selected for the present study because it exhibits very high selectivity toward Pu IV compared to other actinides like Am III and U VI . Earlier, Kannan et al have reported distribution coefficients of 10 4 and 10 for Pu IV and U VI , respectively, in ≥3 M nitric acid medium using 0.2 M solution of N , N ′-dioctyl-α-hydroxyacetamide in dodecane. , The choice of the polypropylene membrane as the polymeric support was based on its highly porous structure that renders easy and fast accessibility of binding sites for actinide sorption and also that polypropylene easily decomposes during TIMS analysis. For TIMS analysis, the supported liquid membrane preloaded with Pu was deposited at the center of a Re filament, in a well-defined and reproducible manner that improved the transport of gaseous ions to the mass analyzer, thereby enhancing the sample utilization efficiency.…”
mentioning
confidence: 99%
“…31,[35][36][37][38][39][40] Scarce studies have been published concerning the extraction properties of these DCs. [43][44][45][46] In one of them, we assessed the different extraction and back-extraction properties of most of them along the different steps of the i-SANEX process. This assessment revealed that a few DCs have similar properties to TODGA, but other DCs extract undesirable elements like fission products (FPs), potentially leading to a reduction in process efficiency.…”
Section: Introductionmentioning
confidence: 99%